(untitled) (Bangladesh Journal of Animal Science, 2018)
An experiment was conducted at AZ-Zahra Farm, Sandakan, Sabah, Malaysia to investigate the productive and reproductive performance of Saanen dairy goat. Body weight at different ages were collected once while birth weight was collected when does gave birth. On the other hand, milk production of each individual per day was received continuously for three months. The data on reproductive parameters such as length of estrus cycle, duration of estrus period, age at puberty, gestation length, age at first kidding, litter size, birth weight and kid mortality were noted. Descriptive statistics such as number, percentage, mean, standard deviation were performed. T-test was also conducted to know the statistical difference between the groups. Result demonstrated that body weight increases significantly (p<0.01) with the advancement of the age. The highest daily milk yield was found in 2-3 years of age. Dam with multiple kids produced more milk than dam with single kid. Estrus cycle of Saanen goats was found 21 days, the average estrus period duration was 2.75 days, age at puberty was 8.33 months, first kidding age was 14.2 months and gestation period was 150 days on an average. With the increase of the age of dam litter size increased. Meanwhile average birth weight increased as age of dam increased from 2.85 kg in 1 year to 3.26 kg in 3 years. Male kids born heavier than females (3.23±0.62 vs. 2.75±0.58 kg) and single kids were heavier than twin kids (3.07±0.66 kgvs2.70±0.28 kg). Low mortality rate of kids was recorded in this study (6.4%). It can be concluded that the overall productive and reproductive performances of Saanen goat at AZ-Zahra farm were within the acceptable level and the variation recorded in different parameters is very much usual. Bang. J. Anim. Sci. 2018. 47 (1): 1-12